Inoculation and phosphorus fertilizer improve food-feed traits of grain legumes in mixed crop-livestock systems of Ethiopia - Belete, Sisay; Bezabih, Melkamu; Abdulkadir, Birhan; Tolera, Adugna; Mekonnen, Kindu; Woldemeskel, Endalkachew (Elsevier, 2019)
Grain legumes play an important role as source of food and feed in smallholder mixed systems. They also contribute to soil fertility improvement through biological nitrogen fixation. Although rhizobium inoculation and phosphorus fertilizer are known to improve grain yield of legumes, information is limited on the effect of this practice on the yield and fodder quality of the haulm. This study was conducted to evaluate the effects of rhizobium inoculation (I) and phosphorus fertilizer (P) on yield and nutritional quality of grains and haulms of grain legumes (faba bean, chickpea, common bean and soybean) on farm across diverse agroecological locations in the Ethiopian highlands. The crops were subjected to four treatments [+I, +P, −I + P and a negative control (-P-I)] at multiple locations on farm during the main cropping season in 2016. Yield data was recorded during grain harvesting, and subsequently representative samples of grains and haulms were collected and analyzed for quality variables. Effects of the treatments were significant (P < 0.05) with 30% increase on grain yield for all studied crops and 28% increase on haulm dry matter yield for faba bean, common bean and soybean. Crude protein (CP) and in vitro organic matter digestibility (IVOMD) values of faba bean, common bean and soybean haulms were higher (P < 0.05); and neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents were lower (P < 0.05) for the treatments than the control. The haulm CP content and IVOMD of chickpea also responded positively (P < 0.05) to the treatments. The current results demonstrated the possibility of improving both yield and quality of grains and haulms of grain legumes with the application of efficient rhizobium inocula and P fertilization. This practice offers an opportunity for smallholders in the crop-livestock system to improve the food-feed traits of grain legumes with minimal input and environmental footprint.